2010
DOI: 10.1111/j.1399-3054.2009.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drought intensity on the response of six woody karst species subjected to successive cycles of drought and rewatering

Abstract: Tolerance to the effects of drought and subsequent recovery after a rainfall appear to be critical for plants in the karst regions of southwestern China, which are characterized by frequent but temporary drought events. This study investigated the effects of drought intensity and repetition on photosynthesis and photoprotection mechanisms of karst plants during successive cycles of drought and subsequent recovery. Leaf water potential, gas exchange, chlorophyll fluorescence and several associated metabolic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 40 publications
4
36
0
Order By: Relevance
“…Therefore excess of precipitation in May and June as well as accumulated water in deeper layers of soil caused high and stabile photosynthesis in July. The reduction of photosynthesis caused by drought occurrence in vegetation period was certainly expected and previously confirmed in many studies [15][16][17]. Comparing the monthly averages of photosynthesis, it could be seen that the highest photosynthetic production was found in July, when the average temperature was about 25.5°C.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore excess of precipitation in May and June as well as accumulated water in deeper layers of soil caused high and stabile photosynthesis in July. The reduction of photosynthesis caused by drought occurrence in vegetation period was certainly expected and previously confirmed in many studies [15][16][17]. Comparing the monthly averages of photosynthesis, it could be seen that the highest photosynthetic production was found in July, when the average temperature was about 25.5°C.…”
Section: Discussionsupporting
confidence: 75%
“…It may also be due to the ample precipitation found in the studied areas (annually around 1000 mm, mainly occurring during the growth season). Liu et al 11 did find that soil water stress (withholding water) affected photosynthesis and growth, and re-watering could remove or alleviate these effects in potted tree seedlings from almost the same karst area as in our study. However, the water stress treatment (withholding water) period in Liu et al's experiment was as long as 20 days.…”
Section: Discussionsupporting
confidence: 69%
“…drought events are repeated, as reported in Liu et al (2010). Evidence that repeated events can impair resilience or resistance was also given by Zavalloni et al (2009), who observed that frequent mild drought events evoked by simulated climate warming enhanced stress levels in grasslands and lowered the resistance to a severe drought event.…”
Section: F E Dreesen Et Al: Resistance To Successive Climate Extremesmentioning
confidence: 70%
“…Lack of sufficient resilience (capacity of an ecosystem to reach pre-disturbance performance levels) can thus compromise resistance (ability of an ecosystem to withstand displacement from control levels) to a subsequent event. The ability to recover not only is species-specific (Gallé et al, 2011;Liu et al, 2010) but is also influenced by competitive interactions, plant age or size (Lloret et al, 2004), the intensity of the past drought (Miyashita et al, 2005), and the amount of stored carbon reserves (Galiano et al, 2011). Importantly, recovery can be delayed when Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%